Impurity of Stem Cell Graft by Murine Embryonic Fibroblasts – Implications for Cell-Based Therapy of the Central Nervous System - Molcanyi, Marek; Mehrjardi, Narges Zare; Schäfer, Ute; Haj-Yasein, Nadia Nabil; Brockmann, Michael; Penner, Marina; Riess, Peter; Reinshagen, Clemens; Rieger, Bernhard; Hannes, Tobias; Hescheler, Jürgen; Bosche, Bert (Frontiers in Cellular Neuroscience, 2014)
Stem cells have been demonstrated to possess a therapeutic potential in experimental models of various central nervous system disorders, including stroke. The types of implanted cells appear to play a crucial role. Previously, groups of the stem cell network NRW implemented a feeder-based cell line within the scope of their projects, examining the implantation of stem cells after ischemic stroke and traumatic brain injury. Retrospective evaluation indicated the presence of spindle-shaped cells in several grafts implanted in injured animals, which indicated potential contamination by co-cultured feeder cells (murine embryonic fibroblasts – MEFs). Because feeder-based cell lines have been previously exposed to a justified criticism with regard to contamination by animal glycans, we aimed to evaluate the effects of stem cell/MEF co-transplantation. MEFs accounted for 5.33% ± 2.81 of all cells in the primary FACS-evaluated co-culture. Depending on the culture conditions and subsequent purification procedure, the MEF-fraction ranged from 0.9 to 9.9% of the cell suspensions in vitro. MEF survival and related formation of extracellular substances in vivo were observed after implantation into the uninjured rat brain. Impurity of the stem cell graft by MEFs interferes with translational strategies, which represents a threat to the potential recipient and may affect the graft microenvironment. The implications of these findings are critically discussed.